CUSTOMER ATTITUDE SEBAGAI PEMODERASI KOREAN WAVE, ONLINE CUSTOMER REVIEW DAN ONLINE CUSTOMER RATING TERHADAP MINAT BELI ULANG SKINCARE SCARLETT - Liantifa, Melifia; Permaisuri, Nur Anisa (LP2M Universitas Bina Bangsa, 2025)
The purpose of this research is to prove the effect Korean Wave, Online Customer Review and Online Customer Rating on Repurchase Intention skincare Scarlett with Customer Attitude as a Moderation in Sungai Penuh City. The respondents in this study were 100 respondents who used skincare Scarlett in Sungai Penuh City. The sampling method in this research is convenience sampling, namely anyone who agrees to provide the required information with the researcher, whether they meet directly or indirectly if the respondent is suitable as a data source. Data collection using google form. The data analysis tools used are Descriptive Analysis, Coefficient of Determination, Moderated Regression Analysis (MRA), and the hypothesis test used is the t test. The research results show that Korea Wave, Online Customer Review, Online Customer Rating, and Customer Attitude partially significant effect on Repurchase Intention, Customer Attitude acts as an intermediate moderating variable Korean Wave against Repurchase Interest, as well as Customer Attitude does not act as an intermediate moderating variable Online Customer Review and Online Customer Rating on Repurchase Intention